2018
DOI: 10.1186/s13049-018-0572-4
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of hypotensive resuscitation in patients with traumatic hemorrhagic shock: a meta-analysis

Abstract: BackgroundDamage control strategies play an important role in trauma patient management. One such strategy, hypotensive resuscitation, is being increasingly employed. Although several randomized controlled trials have reported its benefits, the mortality benefit of hypotensive resuscitation has not yet been systematically reviewed.ObjectivesTo conduct a meta-analysis of the efficacy of hypotensive resuscitation in traumatic hemorrhagic shock patients relative to mortality as the primary outcome, with acute res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 22 publications
0
36
0
7
Order By: Relevance
“…A recent meta-analysis of the current evidence on this subject suggests that hypotensive resuscitation in the appropriately selected patients may have some mortality benefit without excessive risk of AKI. 14 Another approach to hemorrhagic trauma patients can be damage control resuscitation, which includes controlling of hemorrhage, replacement of lost blood and preventing coagulopathy can be applied to reduce the incidence of mortality. 15 Thus, more evaluation of the interaction of hemodynamics and AKI in trauma patients is required to identify appropriate management measures around these characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of the current evidence on this subject suggests that hypotensive resuscitation in the appropriately selected patients may have some mortality benefit without excessive risk of AKI. 14 Another approach to hemorrhagic trauma patients can be damage control resuscitation, which includes controlling of hemorrhage, replacement of lost blood and preventing coagulopathy can be applied to reduce the incidence of mortality. 15 Thus, more evaluation of the interaction of hemodynamics and AKI in trauma patients is required to identify appropriate management measures around these characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Shock and arterial hypotension after TBI may be an indicator for supplementary organ lesions, and a search for supplementary lesions should be performed immediately, as about one third of TBI patients are patients with multiple trauma [5]. A meta-analysis observed a lower mortality in patients with traumatic hemorrhagic shock, receiving hypotensive resuscitation [61].…”
Section: Prehospital and Emergency Carementioning
confidence: 99%
“…It is well known that hemorrhagic shock is a frequently complication in severe multiple trauma patients,which may lead to MODS even death.Hemorrhagic shock has been proposed as an main driver of systemic in ammation,gut barrier disruption,endothelial damage and coagulation dysfunction,all these factors may contributed to the development of MODS [25] .A animal model experiment demonstrated that hemorrhagic shock add to the systemic in ammatory reaction early after multiple trauma,aggravate pulmonary damage and worsen renal and endothelial function,which might lead to the development of early multiple organ dysfunction syndrome [26] .Furthermore,it is by now generally accepted that hemorrhagic shock induced a vicious cycle of outcomes,consisting of hypothermia,acidosis,and coagulopathy-otherwise known as the lethal triad [27] .Besides,hemorrhagic shock can lead to a imbalance between oxygen supply and consumption,and this anoxia result in a change from aerobic to anaerobic metabolism.Lactic acidosis ensues,and if uncorrected,MODS and death follow [28] .Consequently,we regarded hemorrhagic shock as a crucial predictor for developing MODS.…”
Section: Discussionmentioning
confidence: 99%